St. Vincent UHT milk marketing study (Louis Berger International New JerseyUS, 1979)
Determines the size and composition of the market for UHT milk in St. Vincent and in the hotel industry in St. Lucia and Grenada. Defines potential for proposed dairy`s sales of UHT milk at varying retail price levels in the above markets through 1988.
IDS